2019
DOI: 10.1177/0959680119866041
|View full text |Cite
|
Sign up to set email alerts
|

Occupations and the recent trends in wage inequality in Europe

Abstract: We aim to contribute to a better understanding of the role that occupations played in recent trends in wage inequality in some European countries. Using EU-SILC data, we observe that most of the changes in wage inequality between 2005 and 2014 were the result of changes in the distribution of wages within occupations. A longer term approximation using data from the Luxembourg Income Study (LIS) shows similar patterns. We conclude that occupational dynamics did not drive recent trends in wage inequality in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
(32 reference statements)
0
2
0
2
Order By: Relevance
“…There is ample evidence showing that recent increases in income inequality can be explained by wage differentials between occupations—occupational-mean skills, tasks, or social classes (Albertini et al, 2020; Goedemé et al, 2021; Liu and Grusky, 2013; Williams and Bol, 2018; Zhou and Wodtke, 2019), but other authors argue that wage variation within occupations or classes better captures inequality trends (Fernández-Macías and Arranz-Muñoz, 2020). Thus, studying the employment relations and job tasks outlined by the EGP model and the RBTC theory and their potential (and shifting) links could shed new light ‘on the extent to which inequality trends may be due to shifts in the task structure related to technological change, or whether class-based changes in inequality are largely unrelated’ (Williams, 2017: 5).…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence showing that recent increases in income inequality can be explained by wage differentials between occupations—occupational-mean skills, tasks, or social classes (Albertini et al, 2020; Goedemé et al, 2021; Liu and Grusky, 2013; Williams and Bol, 2018; Zhou and Wodtke, 2019), but other authors argue that wage variation within occupations or classes better captures inequality trends (Fernández-Macías and Arranz-Muñoz, 2020). Thus, studying the employment relations and job tasks outlined by the EGP model and the RBTC theory and their potential (and shifting) links could shed new light ‘on the extent to which inequality trends may be due to shifts in the task structure related to technological change, or whether class-based changes in inequality are largely unrelated’ (Williams, 2017: 5).…”
Section: Introductionmentioning
confidence: 99%
“… 6. Furthermore, not being able to differentiate the jobs by sector also misses some key differentials in job quality across subsectors within manufacturing and some services. However, previous research with this approach has shown that occupation is a much more important differentiating factor for job quality than sector (Fernández-Macías and Arranz-Muñoz, 2019). …”
mentioning
confidence: 99%
“…Para gerar um entendimento sobre o como o uso da inteligência artificial pode afetar o mercado de trabalho é necessário dar um passo atrás e identificar na literatura sobre os impactos de mudanças tecnológicas de forma mais genérica. A principal abordagem utilizada para entender esses processos nas últimas décadas tinha como foco o conteúdo das tarefas dos empregos (ACEMOGLU; AUTOR, 2011;AUTOR, 2015;BARBIERI et al, 2020;ARRANZ-MUÑOZ, 2020). Autor, Levy e Murnane (2003) são os responsáveis pela principal hipótese relacionada a essa literatura, segundo a qual as novas tecnologias teriam impacto sobre as tarefas de rotina.…”
Section: Automação Inteligência Artificial E Trabalhounclassified
“…Existe uma ampla literatura que busca entender as consequências das transformações tecnológicas sobre o mercado de trabalho, especialmente focadas nos efeitos sobre diferentes segmentos da força de trabalho dos conteúdos-tarefas 2 dos empregos (ACEMO-GLU;AUTOR, 2011;AUTOR, 2015;BARBIERI et al, 2020;ARRANZ-MUÑOZ, 2020). Especificamente, existe uma produção recente sobre os impactos da adoção de robôs nos mercados de trabalho, tanto em economias desenvolvidas quanto em desenvolvimento, possuindo uma variação nas conclusões(ANTON et al, 2020).Dentro dessa perspectiva, Graetz e Michaels (2018) encontraram um efeito nulo da robotização nos empregos, com a redução dos empregos de baixa qualificação, e um efeito positivo sobre os salários a partir de uma abordagem considerando a variação entre setores e em 17 países desenvolvidos entre 1993 e 2007.…”
unclassified